Improving the Quran Reading Skills of Students at TPQ Fathun Qarib UIN Ar-Raniry Banda Aceh: Implementation of Drill and Peer Tutoring Methods for Iqlab Material - Samad, Sri Astuti A; Suriana Suriana; Munawwarah Samad; Lily Mukhlishah Attamy (DIDAKTIKA, 2025)
Iqlab reading skills are very important for TPQ students, but there are still errors in changing the nun mati or tanwin sound to be similar to the mim reading, there are still things missing. The formulation of the problem is (1) how to apply the combination method (drill and peer tutor) in improving the iqlab reading skills of students at TPQ Fathun Qarib UIN Ar-Raniry Banda Aceh, and (2) whether the combination method (drill and peer tutor) can improve the iqlab reading skills of students at TPQ Fathun Qarib. The method used is Classroom Action Research which consists of 2 cycles, with the stages of planning, implementation, observation, and reflection. The results of the study showed that the application of the combination method (drill and peer tutor) is categorized as very good, with an increase in the percentage of ustadzah activity in cycle I (75%, good), and in cycle II to 97.8% (very good). While the activity of students in cycle I (78%, good), and increased in cycle II to 96.7% (very good). After implementing the combination method, there was an increase in Iqlab reading skills, namely students were able to exchange the nun mati/tanwin sound for mim, hum it, and stretch their lips. This study shows that the combination method (drill and peer tutoring) can improve the Iqlab reading skills of students at TPQ Fathun Qarib UIN Ar-Raniry Banda Aceh.